ISSUES IN THE 2023 NIGERIA PRESIDENTIAL ELECTION: IMPLICATIONS FOR SOCIETAL ADVANCEMENT - Offor , Ugochukwu Ifeyinwa; Chukwuma , Martins Onunkwo (Top Educational Review Journal (TERJ), 2024)
This study examined issues in the Nigeria 2023 presidential election: implications for socioeconomic advancement. Two research questions guided the study; descriptive survey research design was adopted for the study. The population of the study was 23000 academic staff of the public universities in South-East Nigeria. The sample comprised 400 academic staff of the universities. The sample was composed using the simple random method. Data collected were analyzed using the mean. Findings of the study showed that 2023 presidential election in Nigeria was marred by such issues as poor voter turnout, rigging, electoral violence, non-compliance to BVAS, IREV, bastardization of the legal system, poor voter turnout, non-compliance to extant laws/acts, unqualified candidates, ethnic sentiments, religious divisions, and poor election management system; to ameliorate the issues, it was found that voter education, punishment of electoral offenders, implementing electoral laws, independence of the judiciary, properly managed electoral system, transparent law enforcement system, implementation of full scale BVAS and IREV use, Adopting Justice Uwais report (2007) on electoral reforms are ways to ameliorate issues in Nigeria 2023 elections. The study therefore recommends that the full-scale use of technology in the Nigerian electoral system will help eliminate over 70% of the issues that greeted the 2023 presidential elections in the country, and at such a time, it is recommended that the Legislator revisit the 2022 electoral act and close the gap in the act by implementing the full-scale use of BVAS and IREV for result collation